Long-Term Functional Outcomes and Complications of Non-Surgical Management for Clavicular Middle Third Fractures - Mahdi Rezai; Ashkan Khodamoradi; Aidin Mohammad Valipour; Roxana Hessam; Mehdi Mohammadi; Kourosh Javdani Esfahani; Ahmadreza Kheradpishe (Journal of Orthopedic and Spine Trauma)
Background: Clavicle fractures are relatively common, and most often occur in the middle third. Fractures that are not displaced or are displaced with no other indication for surgical intervention are treated supportively. Displaced fractures that have been managed non-surgically have had acceptable outcomes. The goal of this study is to evaluate pain scores, the resumption of daily activities, rates of acceptable healing, non-union, malunion, and the need for additional surgical intervention. Methods: This observational study was conducted on 432 patients with midclavicular fractures who were referred to a high-level trauma center. All patients were treated non-surgically and followed for six months. The primary outcomes were patients’ function or disability, assessed using the Disabilities of the Arm, Shoulder, and Hand (DASH) and University of California, Los Angeles (UCLA) scores. The secondary outcomes included the rate of pain relief, measured by the Verbal Numeric Scale (VNS) score, as well as complications such as malunion, nonunion, and the need for secondary surgical intervention. Results: A total of 432 patients were enrolled. The rates of malunion and nonunion were 63.4% and 2.3%, respectively. Patients with malunion exhibited a higher pain score (P < 0.001). The average UCLA score among patients was 32.53, which corresponds to good and excellent grades; it was significantly lower for those with malunion (P < 0.001). The mean DASH score was 5.92, and there was no significant difference between the two groups regarding malunion and normal union (P > 0.05). Conclusion: Our study demonstrated a low non-union rate, good functionality, and a high rate of satisfaction among patients with middle third clavicle fractures who were treated non-surgically.